ANALISIS KEBIJAKAN NEGARA DALAM TATA KELOLA E-GOVERNMENT - Mansawan, Isak Samuel Kijne; Saiba, Hengky (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Analyzing national policy in e-government governance is crucial given the rapid development of digital technology, which demands efficiency and transparency in government. The transformation towards e-government aims to improve public services, civic participation, and government accountability through the utilization of information technology. However, its implementation often faces challenges such as infrastructure gaps, human resource capacity, and regulatory harmonization. This journal aims to analyze national policy in e-government governance from a governmental perspective, focusing on policy effectiveness, system integration, and its impact on administrative performance. This research employs a qualitative approach through literature review and analysis of policy documents from various countries, including Indonesia, as well as interviews with relevant stakeholders. Data was collected from official government sources, international reports, and academic journals to ensure the validity of the findings. The research results indicate that the success of e-government governance largely depends on political commitment, the availability of technological infrastructure, and the training of civil servants. Countries with integrated and adaptive policies tend to achieve higher efficiency in public services compared to those that adopt a partial approach. In Indonesia, despite significant progress in government digitalization, challenges such as disparity in internet access and inter-agency coordination remain major obstacles. This journal concludes that strengthening regulations, investing in infrastructure, and improving digital literacy are strategic steps to optimize e-government governance. The recommendations provided include the formulation of an inclusive and sustainable national framework to support the digital transformation of government.